Prevalence of skin cancers in kidney transplant recipients - one-center experience - Kosko, Fabian; Dębska-Ślizień, Alicja; Imko-Walczuk, Beata; Piesiaków, Maria Luiza; Biedunkiewicz, Bogdan; Bułło-Piontecka, Barbara; Bzoma, Beata; Chamienia, Andrzej; Gołębiewska, Justyna; Konopa, Joanna; Król, Ewa; Liberek, Tomasz; et al. (Frontiers in Oncology, 2025)
IntroductionNon-melanoma skin cancers (NMSCs) are the most common neoplasms that occur in solid organ transplant recipients (SOTRs). Squamous cell carcinoma (SCC) and basal cell carcinoma (BCC) make up over 90% of skin cancers in SOTRs. Key risk factors include age at transplantation, skin type, immunosuppression, as well as sun exposure (ultraviolet radiation) and viral infections, contributing significantly to tumor development. This study aimed to estimate the incidence and risk of NMSCs in kidney transplant recipients (KTRs) in Poland and to provide new clinical data on patients developing skin cancers in this population.MethodsThis study included 105 KTRs, out of approximately 1,500, who were under the care of the Transplant Outpatient Clinic at the University Hospital in Gdansk between 1980 and 2022 and were diagnosed with NMSC.ResultsA total of 250 cutaneous malignancies were diagnosed in 105 KTRs. BCC (58.8%) and SCC (37.6%) were the most common histological types, and the SCC: BCC ratio was approximately 2:3. Other skin neoplasms, including malignant melanoma (2%) or hidradenocarcinoma, were significantly less frequent. The mean age of KTRs at the time of skin cancer diagnosis was 59.6 years, with a mean time from transplantation to cancer diagnosis of 103.2 months. Most skin cancers were diagnosed 5–10 years post-transplantation and were located on the.24%). The immunosuppressive therapy protocol did not significantly affect the risk of developing skin cancer. The only significant factor associated with an increased risk of skin cancer was patient age. One patient died due to metastatic SCC.ConclusionNMSCs account for 90% of skin cancers in KTRs; they have a high recurrence rate and are most often found on the face of older patients towards the end of the first decade after transplantation. Our study confirms that the risk of further skin neoplasm is high and that SCC can be a cause of death. Early detection not only improves prognosis but also minimizes the extent of surgical interventions, which is particularly crucial for lesions in visible areas.